Intact pks15/1 in Non–W-Beijing Mycobacterium tuberculosis Isolates - Chaiprasert, Angkana (Centers for Disease Control and Prevention, 2006)
To determine whether intact pks15/1 is unique to the W-Beijing family, we investigated 147 Mycobacterium tuberculosis strains with different IS6110 genotypes. Intact pks15/1 was found in 87.8% of cerebrospinal fluid and 84.9% of sputum isolates. It was found not only in W-Beijing strains (≈97%) but also in other genotypes (38.5%–100%).